2x+8+4x-3=

Simple and best practice solution for 2x+8+4x-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+8+4x-3= equation:


Simplifying
2x + 8 + 4x + -3 = 0

Reorder the terms:
8 + -3 + 2x + 4x = 0

Combine like terms: 8 + -3 = 5
5 + 2x + 4x = 0

Combine like terms: 2x + 4x = 6x
5 + 6x = 0

Solving
5 + 6x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 6x = 0 + -5

Combine like terms: 5 + -5 = 0
0 + 6x = 0 + -5
6x = 0 + -5

Combine like terms: 0 + -5 = -5
6x = -5

Divide each side by '6'.
x = -0.8333333333

Simplifying
x = -0.8333333333

See similar equations:

| (4+6)(2+4x)=45-2.5(x+3) | | -6(5-2n)=-6 | | .5b=58 | | y^2+9y+54=0 | | 0=2x^3-x^2-13x-6 | | 5+3(n-4)=2(n+1) | | 8p-5+4=23 | | x^2-5x-2= | | 3y+9x=15 | | -5-3n+6n=-11 | | y=24 | | s*4+8=20 | | (7x^3-8x^2+4)-(2x-7x-8)= | | -21x+7=7x | | 13h+6d-9d-7h= | | (7x^3-9x^2+4)-(2x^3-7x-8)= | | 124-6x=21x+22 | | (2xy^2-5)+(7xy^2+8)= | | z+ 4= 9 | | -3x-2=4x+6 | | (4x^2-9x-7)(5x+9)= | | 8=2a | | 25(x+4)+5x=5.50 | | -5x+3y=9 | | -176=4(6b-2) | | x^3=9x^2-20x | | 3x+3y+2=0 | | 5x+4=45x+8 | | v+5=12 | | x^4+8x^2-11=0 | | -10x^2+12x=-6x^2-2x | | 4(z+15)=5(z+2) |

Equations solver categories